VD_FINDINFO HC / 2012 / 6 vom 23. November 2011 - VD Tribunal cantonal (2011)
CONTRAT DE TRAVAIL, RÉSILIATION IMMÉDIATE, JUSTE MOTIF, MALADIE | 324a al. 1 CO, 336c CO, 337 CO, 337c CO, 337d CO, 308 al. 1 let. a CPC (CH)